O Modelo de Três Equações (IS-PC-MR) em uma estrutura dinâmica Neo-Kaleckiana para uma pequena economia aberta - Pinto, Vitor Hugo Santos (2024)
This dissertation proposes a model that engages in the debate on the theoretical compatibility between the Inflation Targeting Regime (ITR) and a neo-Kaleckian approach. The model incorporates features such as demand-led structure, inflation through distributive conflict and pass-through effect, exogenous functional income distribution, and endogenous monetary rule. Additionally, estimation of a Bayesian Vector Autoregressive Model (BVAR) was conducted, using monthly data from 2002 to 2023. This analysis integrated various variables from the Brazilian and U.S. economies, including the Consumer Price Index, exchange rate, capacity utilization rate, unemployment rate, country risk measured by EMBI, and short-term interest rates from Brazil and the United States. The results emphasize that, under the ITR, capacity utilization is uniquely determined by the value that does not accelerate inflation. Consequently, control over it is relinquished for growth. The real interest rate is used as an endogenous instrument for this control, limiting the scope for policies uncoordinated with the monetary rule. Furthermore, the long-term interest rate is not determined by expectational factors, but rather by the equivalence condition of the international interest rate, added to the risk spread and inflation differential between economies. The real exchange rate, respecting the Marshall-Lerner condition, plays a relevant synergistic role in inflation control.